Penilaian Kebutuhan Home Pharmacy Care Untuk Pasien Diabetes Mellitus Tipe 2 Yang Disertai Hipertensi Pada Usia Lanjut - Yuhansyah Nurfauzi; Djoko Wahyono; Fita Rahmawati; Nanang Munif Yasin (Fakultas Farmasi Universitas Setia Budi, 2020)
Home Pharmacy Care (HPC) expected to be provided by pharmacists for chronic illnesses or the elderly, however, the implementation is still far from the expectations of those who need it. It is the first qualitative study in Indonesia that aims to assess the need for HPC for elderly patients with Type 2 DM accompanied by hypertension in Cilacap. This is a preliminary study for subsequent research to create a model of HPC for elderly. Patient and health care providers’ perspectives were explored to reveal the need for HPC. This research uses qualitative methods and a survey with in-depth interviews. The survey was conducted by distributing questionnaires to pharmacists to describe the activities in HPC, their constraints. and the skills needed to carry them out. The research subjectsconsisted of 32 pharmacists, while the informants consisted of 4 doctors, 3 nurses, and 5 patients that met the saturation of the data. Only 3 pharmacists (9,4%) of the total research subjects have ever provided HPC, while the rest have never done so, however, pharmacists, health workers, and patients stated the need for HPC. Constraints revealed were limited human resources, time and finance. Pharmacists require medication education skills, diet, physical activity and foot examinations accompanied by adequate communication skills. Home pharmacy care is still rarely practiced in Cilacap, but it needs to be implemented selectively because it was supported by doctors, nurses, and patients. The need for HPC was relevant to be followed up with the establishment of a pharmaceutical service model.